Polo-like kinase 4 transcription is activated via CRE and NRF1 elements, repressed by DREAM through CDE/CHR sites and deregulated by HPV E7 protein. Issue 1 (25th September 2013) - Fischer, Martin; Quaas, Marianne; Wintsche, Axel; Müller, Gerd A.; Engeland, Kurt
Abstract: Infection by oncogenic viruses is a frequent cause for tumor formation as observed in cervical cancer. Viral oncoproteins cause inactivation of p53 function and false transcriptional regulation of central cell cycle genes. Here we analyze the regulation of Plk4, serving as an example of many cell cycle- and p53-regulated genes. Cell cycle genes are often repressed via CDE and CHR elements in their promoters and activated by NF-Y binding to CCAAT-boxes. In contrast, general activation of Plk4 depends on NRF1 and CRE sites. Bioinformatic analyses imply that NRF1 and CRE are central elements of the transcriptional network controlling cell cycle genes. We identify CDE and CHR sites in the Plk4 promoter, which are necessary for binding of the DREAM (D P, R B-like, E 2F4 a nd M uvB) complex and for mediating repression in G0 /G1 . When cells progress to G2 and mitosis, DREAM is replaced by the MMB (M yb-M uvB ) complex that only requires the CHR element for binding. Plk4 expression is downregulated by the p53-p21 WAF1/CIP1 -DREAM signaling pathway through the CDE and CHR sites. Cell cycle- and p53-dependent repression is abrogated by HPV E7 oncoprotein. Together with genome-wide analyses our results imply that many cell cycle genes upregulated in tumors by viral infection are bound by DREAM through CDE/CHR sites.